Implementasi Fungsi Manajemen Dakwah Dalam Pembinaan Kemampuan Membaca Al-Qur’an Generasi Muda Di Majelis Qur’an Hj. Supiah - Rafli, Ahmad; Soiman, Soiman (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
This study aims to examine the implementation of the function of da'wah management in fostering the ability to read the Qur'an of the young generation at the Hj. Supiah Qur'an Assembly Using a qualitative descriptive case study approach. Data collection techniques include in-depth interviews, participatory observation, and documentation of students' tilawah values. The results of the study indicate that the implementation of these functions can significantly improve the competence of students in reading the Qur'an, both in terms of tajwid, makhraj, and tilawah rhythm, as evidenced by evaluation scores that are in the "good" to "very good" categories. In addition, coaching also has an impact on strengthening manners, learning motivation, and parental involvement in the education process. This study offers a community-based da'wah management model that can be replicated in similar institutions, and emphasizes the importance of integrating da'wah strategies in strengthening non-formal Islamic education.